Human Resources Recruitment and Selection Process Effectiveness Analysis - Puspitaningrum, Dyah Ayu; Hamida, Nurul Nur; Gunawan, Ahmad (Formosa Journal of Applied Sciences, 2025)
The purpose of analyzing HR recruitment and selection performance is to prove that the business is run by employees best suited to the business needs. The recruitment process is also important to show the strengths and weaknesses in the way of conservation and selection, and to prove that the approach taken is aligned with the company's crucial objectives. The purpose of this study is to assess some of the effectiveness of the human resource management and recruitment process in company A. The method used in this analysis is a sample driven data collection mailing to HR managers and new candidates. The data collected was then analyzed using descriptive statistics and inferential analysis. The results of this analysis explain if the implementation and acquisition series in company A proved to be influential, but there are aspects that must be addressed.